Platynothrus peltifer - van der Hammen, L. (Zenodo, 1959)
Platynothrus peltifer (C. L. Koch, 1839) Nothrus peltifer C. L. Koch, 183g, fasc. 2g (g). Nothrus palliatus C. L. Koch, 183g, fasc. 30 (4). Nothrus bistriatus, Berlese, 18855a, fasc. 17 (g); i88.qc, p. 12. Angelia palliata, Berlese, 1896b, pp. 26, 30, 32. Heminothrus bistriatus, Lombardini, 1936, p. 42. Platynothrus palliatus, Lombardini, 1936, p. 47. Platynothrus peltifer, Sellnick & Forsslund, 1955, p. 515, figs. 17, 18. Berlese described the species in A.M.S. as " Nothrus bistratus Nic. non K." (" Nothrus bistriatus K. " on the plate!). He refers to the species that Nicolet (1855, p. 454, pl. 7 fig. 7) described as a juvenile of Nothrus palustris and which the last-mentioned author (I.e. p. 397) considered identical with Nothrus bistriatus C. L. Koch. (Nicolet's references to N. silvestris, N. palustris, and N. bistriatus are extremely confused). In fact the identity of Nothrus bistriatus C. L. Koch is uncertain; it resembles a Camisia. Berlese (1896b) classified the species (as palliata C. L. Koch) with the genus Angelia; on p. 30 he mentions N. peltifer C. L. Koch as a synonym, and on p. 32 Hermannia bistriata Mich. Nothrus cirrosus Canestrini & Fanzago (1876, p. 100), mentioned by Berlese (1896b, p. 29) as a synonym of Angelia palliata, is of uncertain identity. Platynothrus peltifer is the correct name of the present species; it is found in Europe, Greenland, and Canada. A detailed description was given by Sellnick & Forsslund, 1955, p. 515, figs. 17, 18. According to Lombardini (1936) the specimens in the Berlese Collection are identified as Heminothrus bistriatus and Platynothrus palliatus. I have paid, however, no attention to the preparations of this common species. Published as part of van der Hammen, L., 1959, Berlese's Primitive Oribatid Mites, pp. 1-93 in Zoologische Verhandelingen 40 on pages 71-72